A Brief Explanation of Consumer Bankruptcy and Aspects of the Bankruptcy Estate in the United States of America - Evans, Roger G (Comparative and International Law Journal of Southern Africa, 2010)
The American bankruptcy law system is considerably different from most other bankruptcy regimes. In place of the policy of advantage to creditors, which is the system prevailing in most western countries, and also in South Africa, the American system places considerable emphasis on the fresh start policy. While this policy assists debtors to build up a new estate by allowing them to keep a considerable number of their assets, the creditors are also looked after because of the further policy of the preservation of the bankruptcy estate, thereby possibly swelling the bankruptcy estate of the debtor. The exclusion of the debtor’s assets from his or her bankrupt estate is known as exemption law. But whatever the policy, bankruptcy (insolvency in some jurisdictions) is, however, really a hopeless situation for all the parties involved, such as the creditors, the debtor, the state, and society in general. For this reason, some commentators submit that the debtor should be forgiven. This may be a sensible idea because if the fresh start policy is ignored in a bankruptcy system, a debtor may become a debt slave who is never able to escape from debt. He or she may then have to depend on social hand-outs, thereby ultimately placing a burden on the country’s social system.